Identifikasi Toleransi Kekeringan Tetua Padi Hibrida pada Fase Perkecambahan Menggunakan Polietilen Glikol (PEG) 6000 - Widyastuti, Yuni; Purwoko, Bambang Sapta; Yunus, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTDeveloping of  drought tolerant hybrid rice varieties requires parental lines which have tolerance to drought. Polyethylene glycol (PEG) has been widely used as an osmotic solution for detecting drought tolerance at germination stage of rice. The objectives of this experiment were to evaluate variables of drought tolerance at germination stage  and to select drought tolerance of parental lines using osmotic solution PEG 6000 at concentration of 25%. The experiment was conducted at the greenhouse ICABIOGRAD Cimanggu Bogor, during April-May 2014. The design of the experiment was arranged in factorial randomized block design with three replications. The first factor (genotype) had 21 levels and the second factor (osmotic potential) had two levels (0 and 25% concentration levels of PEG 6000). Based on the principal component analysis, six primary indicators were proposed for drought tolerance of rice at germination stage, i.e., germination percentage, seed vigor, seminal root length, seedling length and dry weight of seminal root. Based on the clustering analysis, at 73.76% of similarity rate, the 21 tested genotypes were divided into 2 groups. The genotypes which showed similar responses with Salumpikit were IR 58025B, GMJ 14B, IR 80154B, GMJ 15B, R 3, PK 90, and PK 12 respectively. Keywords: drought tolerance, germination, hybrid rice PEG, parental lines